A prática do preparo e administração de insulina realizada pelo cliente diabético ou responsável no CIDH de Barbalha - Alencar, Ana Maria Parente Garcia (2004)
This is a descriptive and quantitative study with bearers of diabetes types 1 and 2, their relatives and nursing auxiliaries. This investigation aims at: characterizing the group studied according to socio-demographic variables and insulin treatment; describing the preparation and administration of insulin, keeping, refrigeration and reusing of syringes and needles done by CIDH users and observing the educative orientation about preparation and administration of insulin by nursing. An interview and a systematic observation of the study’s participants were held as a data collection instrument. One concluded that from the total of the participants: 62% are female, 25% are in the 61-70 age group, 44% are married, 39% come from Barbalha, 39% did not finish high school, 46% are retired, 40% earn two salaries a month and 40% live with spouses and children. The majority, 72%, are DM2. The data show that: 55% of the diabetes bearers inject themselves with insulin; 57% learned how to inject insulin with nurses; 100% change the place of application; 13% showed skin alteration; 53% do not show discomfort on the insulin’s application; 89% keep the insulin’s bottles on lower shelves or on the refrigeratohs door. The diabetes bearers and/or their relatives had difficulties with their learning due to fear, preparation of NPH and regular insulin, bad visualization of needle graduation’s scales, technique of putting air in the preparation and visual disability; as to facilities, they mentioned the use of plain and clear language, the orientations in workshops and lectures, interest, necessity of independence, interaction, incentive and stimuli, attention and kindness of the people who gave orientations. As to insulin preparation: 53,8% of the participants do not wash their hands; 62% do not wash the insulin bottles; 96,7% do the correct homogenization of NPH insulin; 84,9% remove the needle protector correctly; 75% do the vacuum prevention stage, 83,3% aspirate the correct insulin’s dose; 91,85 remove the air bubbles from the syringe. As to insulin’s application, 76,9% clean the skin with antiseptic; 98,9% do the cutaneous pleat; 96,7% do the correct needles’ angle, 52,7% do not aspirate the insulin before its introduction, 58% wait some seconds before removing the needle from the skin, 94,6% do not massage the area after the procedure. As to educative orientation, one could verify that the professionals who do it have a great technical knowledge about the scientific aspects studied, however, there is a gap in teaching pedagogical techniques and there is lack of interaction between the people involved, few participation of clients, during the orientation sections and during their planning. The data obtained should be analyzed by nurses, aiming to enhance the nursing assistance to this clientele, through rethinking of educative orientations’ practice done.